Diseminasi Informasi Mengenai Tumbuhan Liar Pekarangan yang Berkhasiat Obat sebagai Alternatif Pemeliharaan Kesehatan pada Masa Krisis Ekonomi di Desa Jeringo, Kabupaten Lombok Barat - Baiq Farista; Arben Virgota; Hilman Ayadi; Dining Candri (Universitas Mataram, 2021)
In the last few years, the use of medicines made from natural ingredients has returned to people's consumption today because of the assumption that natural ingredients are safer and more economical than chemical drugs. The assumption that natural medicine is safer than chemical drugs. Medicinal plants are types of plants in which certain parts of the roots, stems, bark, leaves or excretions are believed to relieve or reduce pain. Several types of wild medicinal plants found in Jeringo Village are meniran (Phyllanthus urinaria), cat whiskers (Orthosiphon aristatus), bebele / gotu kola (Centella Asiatica), shy daughter (Mimosa pudica) and horse whip (Stachytarpheta jamaicensis). The purpose of this activity is to introduce several types of wild plants that have medicinal properties that grow in the yard, along with how to maintain and process them. It is hoped that from this activity the people of Jeringo will have knowledge and be able to carry out treatment independently by utilizing wild plants as one of the cheap and safe alternative treatments.